2016
DOI: 10.1177/1060028016657839
|View full text |Cite
|
Sign up to set email alerts
|

Drug Class Combination–Associated Acute Kidney Injury

Abstract: Our study demonstrates a lack of well-designed studies addressing drug class combination-associated AKI. The combination of NSAIDs and diuretics with or without additional renin-angiotensin aldosterone agents had the strongest level of evidence. Despite limitations, the information included in this review may result in additional scrutiny about combining certain individual nephrotoxic drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 109 publications
(124 reference statements)
0
18
0
1
Order By: Relevance
“…Antibiotics were present also in a minority of our patients and this low number precluded us to infer their responsibility in CA-AKI. Regarding diuretics, there are surprisingly few studies which focus on their role in inducing AKI, especially when they are combined with renin-angiotensin system (RAS) blockers [ 15 ]. Fifty-two percent of our patients with AKI had diuretics and they were associated (mainly in fixed dose combinations) with RAS blockers in one quarter of the patients with CA-AKI.…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotics were present also in a minority of our patients and this low number precluded us to infer their responsibility in CA-AKI. Regarding diuretics, there are surprisingly few studies which focus on their role in inducing AKI, especially when they are combined with renin-angiotensin system (RAS) blockers [ 15 ]. Fifty-two percent of our patients with AKI had diuretics and they were associated (mainly in fixed dose combinations) with RAS blockers in one quarter of the patients with CA-AKI.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the higher intratubular levels of uric acid may produce crystal deposition, inflammation and oxidative stress [69]. SGLT2 inhibition is also associated with shift of oxygenation from medulla to cortex; this effect may predispose DM2 patients to AKI when they are exposed to additional injuries, such as contrast media, NSAIDs, volume depletion [70,71,72]. Hence, an accurate evaluation of volemic status and screening of potential kidney toxins should be a preliminary step in patients undergoing SGLT2-i therapy.…”
Section: Adverse Effects Of Sglt2 Inhibitorsmentioning
confidence: 99%
“…Our study found that the combinations of codeine phosphate with metoclopramide, zopiclone, prednisone and the medication combination amoxicillin and clavulanic acid increase the risk of AKI. A systematic review concluded a lack of well‐designed studies addressing medication class combination associated with AKI . The systematic review found that there is only evidence to support the combination of NSAIDs and diuretics with or without additional renin‐angiotensin aldosterone agents, contributing to AKI, but the evidence to support other medication combinations with AKI is inadequate.…”
Section: Discussionmentioning
confidence: 99%
“…AKI in older adults is associated with an increased risk of mortality, lower health‐related quality of life, and increased length of hospital stay . A systematic review of the literature concluded that the quality of evidence of medication combinations and their association with the development of AKI is weak . In addition, there is limited population‐level evidence available on the medication combinations associated with AKI.…”
Section: Introductionmentioning
confidence: 99%